Accelerated Rauhut-Currier dimerization enabled the synthesis of (+/-)-incarvilleatone and anticancer studies - Kotammagari, Tharun K.; Misra, Sweta; Paul, Sayantan; Kunte, Sunita; Gonnade, Rajesh G.; Santra, Manas K.; Bhattacharya, Asish K. (Beilstein Journal of Organic Chemistry, 2023)
The total synthesis of racemic incarvilleatone has been achieved by utilizing unexplored accelerated Rauhut-Currier (RC) dimeriza-tion. The other key steps of the synthesis are oxa-Michael and aldol reactions in a tandem sequence. Racemic incarvilleatone was separated by chiral HPLC and the configuration of each enantiomer was determined by single-crystal X-ray analysis. In addition, a one-pot synthesis of (+/-)-incarviditone has been achieved from rac-rengyolone by using KHMDS as a base. We have also assessed the anticancer activity of all the synthesized compounds in breast cancer cells nonetheless, they exhibited very limited growth suppression activity.
Keywords: dimerization; incarviditone; incarvilleatone; oxa-Michael; Rauhut-Currier